Pengembangan Bahan Ajar Dongeng Berbasis Kearifan Lokal Kediri untuk Siswa Kelas III Sekolah Dasar - Rahmadanty, Risma Desya; Laila, Alfi; Saidah, Karimatus (Universitas Nusantara PGRI Kediri, 2022)
This research was conducted to: (1) determine the validity of product development of fairy tale material-based Kediri local wisdom and (2) determine the effectiveness of product development of fairy tale material-based Kediri local wisdom. The research method used R&D. The technique of collecting data used questionare validated by the experts. Data analysis was carried out by testing the validity and the effectiveness. The results of this research were: First, from the material expert showed that the product validity got score 94% and 92% from teaching materials expert. It can be said that teaching material was very valid. Second, the results of the effectiveness of fairy tale teaching material showed that pre-test was 45.52% and post-test was 87.5%. The normality test on a limited scale got 0.676 of pre-test score and 0.334 of post-test score. While on a wide scale, pre-test score was 0.680 and post-test was 0.219. Out of these results showed that it was significant > 0.05, so the data was normally distributed. In the homogeneity test obtained 0.067> 0.05, it can be said that the data was homogeneous. The result of t-test was 0.000 <0.05. It means that teaching material for fairy tales is very effective. The results of this study are important as a basis for developing fairy tale material in elementary school.